Respuesta de seis líneas F6 de arroz (Oryza sp.), ante los patógenos frecuentes del tallo y del grano, en la zona de Yaguachi, provincia del Guayas, Ecuador - García Sánchez, Alvaro Marcelo (2021)
This research was carried out in the coastal region, Guayas province, San Jacinto de Yaguachi canton, located at Latitude: 2 ° 5'48.5 '' S and Longitude: 79 ° 41'41.4 '' W; it has a territorial extension of 512.56 km². Its cantonal head is located 20 km from Guayaquil, Ecuador, located at 15 m.s.n.m, mean annual temperature 24.5 - 26 ° C and mean annual rainfall 750 - 1342 mm. Six advanced F6 rice lines were used as plant material, of which four lines are derived from crosses of Oryza rufipogon G. x Oryza sativa L. ssp. japonica, two lines derived from japonica crosses, four parental lines and two commercial varieties (SFL-011 and FL Arenillas). The study factor was to evaluate the incidence and severity of frequent stem and grain pathogens in six advanced F6 lines of rice. In this study, the means comparison of the of the diseases incidence in the segregating populations of rice and controls cultivars, was carried out through a completely randomized block design with twelve treatments and four repetitions, the Tukey test 95% scatter grams and frequency analysis. To find the disease index (IE), a formula was used in which it represents both the incidence of the disease and the severity of symptoms IRRI (2002), after calculating the disease index (IE), the performed Analysis was the Relative Variability (%), in order to identify the lines that were less affected by the diseases evaluated in this study, for which an excel table formula was used, to represent the values in a scatter graph. To carry out this study, several agronomicals labors were carried out such as: land preparation, irrigation, fertilization, control of pest insects, weed control (manual), except the application of fungicides. Parametric visual evaluation tables were used to evaluate the diseases, in which the damage and severity scales of the different diseases that were evaluated during the cultivation phase are found. In addition, laboratory samples were collected in order to identify the causative agent. Relating the diseases evaluations ,the analysis of variance, it was evidenced that there is statistical significance, in: percentage of grain staining, number of panicles per plant, grains per panicle, percentage of sterility, plant gram yield, which indicates that the diseases evaluated in this study have a negative effect on performance decline. The relative variability (%) analysis was used for the selection of lines with a lower degree of infection, in which 6 lines less affected response were identified, within there are 2 treatments that show less affectation by diseases such as T9 PARENTAL PUYÓN, which shows tolerance to Rhizoctonia oryzae, T2 PUYÓN / JP002 P8-30552 shows tolerance to Sarocladium, and line T12 PARENTAL JP003, shows resistance to Gaeumannnomyces, and grain staining, in the analysis the control T7 SFL- 011 COMERCIAL, showed that it is moderately tolerant to Rhizoctonia oryzae, and Sarocladium oryzae, while T8 ARENILLAS COMERCIAL, is susceptible to the complex of grain staining according to IE.